2010
DOI: 10.1007/s11664-009-1070-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Analysis of the Sn-Ag-Cu-In Solder Alloy

Abstract: The tin-based alloy Sn-1.5Ag-0.7Cu-9.5In (composition in wt.%) is a potential candidate for lead-free soldering at temperatures close to 200°C due to the significant amount of indium. Samples of Sn-1.5Ag-0.7Cu-9.5In were prepared by controlled melting of the pure elements, followed by quenching to room temperature. The samples were analyzed by scanning electron microscopy/ energy-dispersive x-ray spectroscopy (SEM/EDS) and electron backscatter diffraction. The solidified melt consisted of four different phases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…The melting point of a traditional Sn-Pb solder is only 183 • C. In order to decrease the melting point of Sn-Ag-Cu alloys, additional elements in low concentrations are needed. Bismuth and indium are potential candidates that may significantly lower the melting of the Sn-Ag-Cu eutectic [4][5][6][7][8][9]. Furthermore, it was found that the wetting angle between the solder and copper substrate decreases with increasing indium concentration [10].…”
Section: Introductionmentioning
confidence: 99%
“…The melting point of a traditional Sn-Pb solder is only 183 • C. In order to decrease the melting point of Sn-Ag-Cu alloys, additional elements in low concentrations are needed. Bismuth and indium are potential candidates that may significantly lower the melting of the Sn-Ag-Cu eutectic [4][5][6][7][8][9]. Furthermore, it was found that the wetting angle between the solder and copper substrate decreases with increasing indium concentration [10].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 34 shows calculated activity of Sn for an intersection x(Ag) -x(Cu) = 0 at 1300 K. The calculation agrees with experi- Besides a comparison of the calculated phase equilibria and thermodynamic properties with experimental data, the solidification path of promising lead-free solder was compared with differential thermal analysis (DTA) results as well as with literature information. 117 The quaternary alloy Sn-1.5Ag-0.7Cu-9.5In (wt.%) was chosen to check by DTA experiment. It is worth adding here that the same sample composition was used in Sopousek et al's 117 work.…”
Section: Resultsmentioning
confidence: 99%
“…Thermodynamic properties of the liquid phase were determined by Fitzner, 111 Jendrzejczyk-Handzlik et al, 112 Popovic and Bencze, 113 who determined the activity of elements in the liquid phase, and Li et al, 114 who measured the mixing enthalpy of the liquid phase. The phase equilibria of the ternary Cu-In-Sn system ware determined by Liu et al 115 and Lin et al 116 The quaternary system Ag-Cu-In-Sn was examined only in a tin-rich corner by Sopousek et al 117 as a potential solder material.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason is, tin-rich alloys based on this system can be used as lead-free solders [4]. There is a number of works regarding TA of Sn-Ag-Cu alloys [3,[5][6][7][8][9][10][11][12][13][14][15][16] but complex analysis of melting and solidification characteristics in a wide range of temperatures and concentrations is still missing. Most of these works concentrate on tin-rich corner of Sn-Ag-Cu system.…”
Section: Introductionmentioning
confidence: 99%